2013
DOI: 10.1097/mcp.0b013e3283642c47
|View full text |Cite
|
Sign up to set email alerts
|

Common variable immunodeficiency-associated granulomatous and interstitial lung disease

Abstract: In a considerable number of patients, ILD is stable over years and patients may not need any immunosuppressive treatment. Prednisone treatment is often used as the first-line treatment and studies suggest response to treatment in 50-66% of cases. In progressive disease with lung function impairment, combined immunosuppressive treatment is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 28 publications
4
50
0
7
Order By: Relevance
“…Similarly, it has been recognised that early diagnosis of GL-ILD in CVID is essential for improved morbidity and survival 8 9…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been recognised that early diagnosis of GL-ILD in CVID is essential for improved morbidity and survival 8 9…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common serious primary immunodeficiency with a prevalence of 1: 25000 – 50000 [1]. In a small minority of patients, single gene mutations resulting in B and T lymphocyte dysfunction have been identified [2].…”
Section: Introductionmentioning
confidence: 99%
“…The differential diagnosis of DLPD in the context of CVID is diverse and includes infection, hypersensitivity pneumonitis, cryptogenic organizing pneumonia, lymphoma and a constellation of radiological-pathological findings known as granulomatous and lymphocytic interstitial lung disease (GLILD) [1,8,9]. Although GLILD is the most common cause of DLPD in CVID, the histopathological features of this disorder are incompletely characterized.…”
Section: Introductionmentioning
confidence: 99%
“…13 Similarly, human herpesvirus-8 was associated with GLILD in one study, 28 though this has not yet been confirmed. Non-infectious pathogenic mechanisms for the development of CVID lung disease have also been proposed, including aberrant B cell lymphoproliferation 29 and T cell-driven autoimmunity. 14 Through retrospective chart review, we found bronchiectasis to be associated with history of pneumonia and reduced CD4+ T cells in CVID.…”
Section: Introductionmentioning
confidence: 99%